Isolasi dan Uji BSLT Ekstrak Etil Asetat Daun Meranti Sabut (Shore Ovalis (Korth.)) - Enda Mora; Musyirna Rahma Nst; Emma Susanti; Arfan Zasliadi (Fakultas Farmasi Universitas Andalas, 2015)
Isolation and test of Brine Shrimp Lethality Test (BSLT) of ethyl acetate extract of Shorea ovalis [Kort.]) leaves have been done. The isolation method used was column chromatography by Step Gradient Polarity (SGP). The aim of this research was to isolate the metabolite secondary compound and examine the activity test of Brine Shrimp Lethality Test (BSLT) from ethyl acetate extract of Shorea ovalis [Kort.]) leaves. The result showed that pure compound was I¬A which characterized by spectrum of IR, H-NMR, C-NMR, HSQC, HMBC and colour reaction of Liebermann-Burchard test. The characterization of the isolate was phytosterol with estimated molecular formula C27H48O. Result of BSLT test revealed that of ethyl acetat extract of meranti sabut leaves at 100, 10, and 1 ppm had value of LC50= 40.45 ppm with death of larva of Artemia salina equal to 56,6 % and was considered as very toxic.